PENERAPAN MEDIA PEMBELAJARAN AUGMENTED REALITY (AR) DALAM PEMBELAJARAN TEMATIK UNTUK MENINGKATKAN HASIK BELAJAR SISWA - Nur Hidayah nur hidayah; Ayu Nizahiroh; Riska Yulianti; Muhammad Swignyo Prayogo (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
This study aims to describe the application of Augmented Reality (AR) learning media in thematic learning to improve student learning outcomes based on a literature review of various previous studies. The research method used is a literature review, which involves analyzing a number of scientific articles and relevant research results regarding the use of AR media in learning in elementary schools. Based on the results of the literature review, it is known that AR-based learning media can help students understand the material more concretely and interestingly because it can display three-dimensional objects that appear as if they are in the real world. AR also increases student interactivity and engagement during the learning process, thereby having a positive impact on their learning outcomes. Several studies show that the application of AR media in thematic learning is effective in strengthening concept understanding, improving memory, and fostering students' interest in learning. Thus, it can be concluded that the use of Augmented Reality (AR) media in thematic learning has great potential to improve student learning outcomes in elementary schools.